2017
DOI: 10.3390/app7121263
|View full text |Cite
|
Sign up to set email alerts
|

A New Compact Octagonal Shape Perfect Metamaterial Absorber for Microwave Applications

Abstract: Abstract:A new compact octagonal shape perfect metamaterial absorber (PMA) design, numerical simulation, fabrication, and investigational verification of unit cell that is based on a simple structure are presented in this paper. The suggested structure comprised of three layers, in which interact to produce the plasmonic resonances. The finite-integration technique (FIT) based Computer Simulation Technology (CST) microwave electromagnetic simulator was utilized to examine the design parameters and conduct abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Metamaterial innovation can be employed to undertake the subject of electromagnetic energy harvesting by viably constructing more productive absorbers. These have on account of they have remarkable properties, for example, negative permeability, left-handed properties, negative refraction and evanescent wave amplification which cannot be found in natural materials [ 2 , 3 ], invisible cloaks [ 4 ], perfect lens [ 5 ], and a perfect absorption [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial innovation can be employed to undertake the subject of electromagnetic energy harvesting by viably constructing more productive absorbers. These have on account of they have remarkable properties, for example, negative permeability, left-handed properties, negative refraction and evanescent wave amplification which cannot be found in natural materials [ 2 , 3 ], invisible cloaks [ 4 ], perfect lens [ 5 ], and a perfect absorption [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table II illustrates the proposed unit cell resonator's comparative view with other reported articles in relevant applications. Most of the authors reported absorption without sensing [31][32][33][34][35][36], whereas the proposed unit cell simultaneously demonstrated the reflection and sensing ability. Therefore, with further precise development and analysis, the resonator cum sensor would be a potential candidate for liquid sensing.…”
Section: Sensing Analysismentioning
confidence: 99%
“…Therefore, diverse techniques and designs have been proposed to enhance the bandwidths, such as modifying the resonator structure, lumped elements resonators, layered structure, and frequency selective surface (FSS), among others 4 7 . High absorption and narrowband responses can clarify some design variations with a closed-ring shape, octagonal shape, resistive-load imposing, and some ring variations 8 , 9 . Unfortunately, higher ohmic loss and bandwidth constraints persist on the suggested unit cell, rendering them unsuitable for microwave applications.…”
Section: Introductionmentioning
confidence: 99%